Evaluating the Construct of Damage in Systemic Lupus Erythematosus. Issue 5 (20th December 2022) - Johnson, Sindhu R.; Gladman, Dafna D.; Brunner, Hermine I.; Isenberg, David; Clarke, Ann E.; Barber, Megan R. W.; Arnaud, Laurent; Fortin, Paul R.; Mosca, Marta; Voskuyl, Alexandre E.; Manzi, Susan; Aranow, Cynthia; et al.
Abstract : Objective: The Systemic Lupus International Collaborating Clinics (SLICC), American College of Rheumatology (ACR), and the Lupus Foundation of America are developing a revised systemic lupus erythematosus (SLE) damage index (the SLICC/ACR Damage Index [SDI]). Shifts in the concept of damage in SLE have occurred with new insights into disease manifestations, diagnostics, and therapy. We evaluated contemporary constructs in SLE damage to inform development of the revised SDI. Methods: We conducted a 3‐part qualitative study of international SLE experts. Facilitated small groups evaluated the construct underlying the concept of damage in SLE. A consensus meeting using nominal group technique was conducted to achieve agreement on aspects of the conceptual framework and scope of the revised damage index. The framework was finally reviewed and agreed upon by the entire group. Results: Fifty participants from 13 countries were included. The 8 thematic clusters underlying the construct of SLE damage were purpose, items, weighting, reversibility, impact, time frame, attribution, and perspective. The revised SDI will be a discriminative index to measure morbidity in SLE, independent of activity or impact on the patient, and should be related to mortality. The SDI is primarily intended for research purposes and should take a life‐course approach. Damage can occur before a diagnosis of SLE but should be attributable to SLE. Damage to an organ is irreversible, but the functional consequences on that organ may improve over time through physiological adaptation or treatment. Conclusion: We identified shifts in the paradigm of SLE damage and developed a unifying conceptual framework. These data form the groundwork for the next phases of SDI development.